An iron–oxygen intermediate formed during the catalytic cycle of cysteine dioxygenase. Issue 57 (14th June 2016) - Tchesnokov, E. P.; Faponle, A. S.; Davies, C. G.; Quesne, M. G.; Turner, R.; Fellner, M.; Souness, R. J.; Wilbanks, S. M.; de Visser, S. P.; Jameson, G. N. L.
Abstract : Combined spectroscopic, kinetic and computational studies provide first evidence of a short-lived intermediate in the catalytic cycle of cysteine dioxygenase. Abstract : Cysteine dioxygenase is a key enzyme in the breakdown of cysteine, but its mechanism remains controversial. A combination of spectroscopic and computational studies provides the first evidence of a short-lived intermediate in the catalytic cycle. The intermediate decays within 20 ms and has absorption maxima at 500 and 640 nm.